Enhancing mathematical problem-solving ability through project-based learning: A study of vocational high school student - Jatisunda, Mohamad Gilar; Suryadi, Didi; Prabawanto, Sufyani (Universitas Hamzanwadi, 2024)
This study aims to improve the mathematical problem-solving ability of students at Vocational High School (VHS) through implementing Project Based Learning (PjBL). The research method used was a quasi-experiment with a matching-only pretest-posttest control group design, with a sample of 64 students divided into two classes, namely experimental and control classes, each consisting of 32 students. The sampling technique used was purposive sampling, where the sample was selected based on specific criteria relevant to the research objectives. Data were collected using tests of mathematical problem-solving ability administered before (pre-test) and after (post-test) the treatment. Data were analyzed using an independent sample t-test and a two-way ANOVA test with univariate general linear model (GLM) analysis. The results showed a difference between the experimental and control groups before the treatment. However, after the treatment, the experimental group had higher mathematical problem-solving ability than the control group, including the improvement and interaction between PjBL implementation and the Early Mathematics Skills (EMS) category.